Case Study: Anesthesia for Congenital Cyanotic Heart Disease With Cerebral Abscess. (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Congenital Cyanotic Heart diseases refer to a bundle of different heart defects that present at birth. The result is low blood oxygen level. Cyanosis refers to bluish coloration of skin and mucus membrane. The purpose of the study to disseminate our knowledge and experience of clinical characteristics, presentation and treatment of the issue for readers as future reference.Case Presentation:  In this case presentation, the anesthetic management of a 2year old baby on 28th September 2024, in Chittagong Medical College Hospital, who was diagnosed with an untreated Tetralogy of Fallot (TOF) complication a brain abscess, is described. Given the intricate relationship between the child's cardiac and neurological conditions, the  patient's presentation of a brain abscess necessitated cautious evaluation of anesthesia.Conclusion: Specialized anesthetic techniques are vital for maintain hemodynamic stability, preventing additional hypoxemia and achieving successful operation. JCMCTA 2025 ; 36 (2) : 168-172